An analysis of the competitiveness of leather and footwear industry in Vietnam - Tran Thi Viet Phuong; Tang, John C.S.; Dimmitt, Nicholas J.; Donyaprueth Krairit; Project 300, People Committee of HCMC, Vietnam (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
The transition of production taking place in worldwide extent is a nature of globalization. In the light of globalization, competition became boundless and increasingly tough between developing economies due to their similar profiles of development. Leather and footwear industry is a typical case for the countries to exploit their inherent factors of advantage. These advantages does not sustain however. This research is to assess the competitiveness of leather and footwear industry in Vietnam since that competitiveness appears not sustainable. Assessing the competitiveness with the help of measurements such as market share, external trade performance, growth of sales, labor cost and price are the fundamental research, which conceals the current highly competitive position of the industry compared to worldwide. The insights are supplemented with highlights of the clustering system implemented. The recommendations show the opportunities for better competitive advantages potential above all for management process. The results of this research are believed helpful in distributing a way out for the leather and footwear industry in Vietnam. In addition, the conceptual framework can be applicable for other industries as well
Submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Keywords: Footwear industry -- Vietnam; Leather industry and trade -- Vietnam